Trinidad B.W.I. - (:unkn) unknown (My University, 2009)
Image of a coastal scene in Trinidad with a coconut palm in the foreground
Black and White; Landscape
Keywords: Postcards; Trinidad and Tobago; Beaches; Coastal scenery; Coconut palm